LAKI-LAKI ATAU PEREMPUAN, SIAPA YANG LEBIH CERDAS DALAM PROSES BELAJAR? SEBUAH BUKTI DARI PENDEKATAN ANALISIS SURVIVAL - Anwar, Samsul; Salsabila, Inas; Sofyan, Rahmadaini; Amna, Zaujatul (Jurnal Psikologi, 2019)
This study aims to compare the level of intelligence between male and female, especially in the learning process in college. Someone who could complete their undergraduate study with a shorter period of time is assumed to have a higher level of intelligence. This research was conducted on Syiah Kuala University students who graduated on the second period of 2017 with a population of 758 people. The number of samples used was 262 people that were determined through Slovin formula with a margin error of 5%. The sampling technique used was Stratified Random Sampling with scientific disciplines as the basis for population stratification. The data analysis method used was the Cox Proportional Hazard (Cox PH) model to find a graduation hazard ratio based on gender and scientific disciplines variables. This study showed that female students have 125.5% potential to graduate faster compare to male. More detail, female students have the potential of 127% to graduate faster on the field of social science, economics and humanities, and 123.9% on the field of sciences and technology. Survival analysis also showed that female student has higher probability to be able to complete their studies faster. Accordingly, it can be concluded that female have a higher level of intelligence than male, especially in the learning process in college.